Unboxing feelings: measuring iPhone happiness through sentiment - Yusof, Rozianiwati; Hashim, Norhafizah; Abdul Rahman, Normaziah; Mohd Yunus, Sri Yusmawati; Aziz Fadzillah, Nor Azlina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The iPhone is widely recognised as a symbol of innovation and technological advancement, yet user discussions often highlight concerns such as pricing, battery life, and camera quality. This study applies sentiment analysis using natural language processing (NLP) to classify user feedback from reviews, forums, and social media as happy or unhappy, enabling the development of an accurate classifier model to measure overall satisfaction and identify recurring themes in user opinions at scale.